A new approach to HLA typing designed for solid organ transplantation: epityping and its application to the HLA‐A locus. (16th April 2013) - Lougee, E.; Morjaria, S.; Shaw, O.; Collins, R.; Vaughan, R.
Summary HLA‐specific antibodies bind discrete clusters of amino acids called epitopes, but serological assignment of antibody specificities makes no reference to this. As HLA typing for solid organ transplantation is provided at only medium (serologically equivalent) resolution, this means that recipient HLA antibodies to donor HLA epitopes may not be identified. We have designed a novel and rapid HLA‐A epitope typing method (epityping) using a two‐stage PCR‐SSP‐based method to detect the HLA‐A locus epitopes described by El Awar et al. 2007, Transplantation, 84, 532. The initial PCR step utilizes HLA‐A locus‐specific primers; the product is cleaned using the QIAquick Spin Purification procedure. The purified product is tested using our in‐house epitope‐specific primer panel, the results being visualized using gel electrophoresis. Twenty two UCLA DNA Exchange samples were epityped, blinded to the HLA type. Of the 75 primer pairs, the mean correlation coefficient was 0.95 with each sample giving 67 or more correct primer results. In all cases, it was possible to derive the first field classic HLA type from the epityping results. These results indicate that a method for identification of HLA epitopes which is comparable in time, cost and technical expertise to current HLA typing methods is achievable. Redesigning HLA typing to correlate with what the antibody binds should minimize inappropriate organ allocation. We suggest that epityping provides a more effective method than standard HLA typing for solid organ transplantation.